The Utilization of WhatsApp on Journalistic Practices of Harian Sumut Pos - Andini Nur Bahri (Program Studi Komunikasi Penyiaran Islam Fakultas Dakwah dan Komunikasi, 2019)
Abstract: The existence of mobile chat applications is one proof of technological and communication development. One popular chat application, WhatsApp, allows journalists to gain information and data needed to help the journalistic practices. The goal of this study is to examine the utilization of WhatsApp on journalistic practices implemented in Harian Sumut Pos. The results of the study show that WhatsApp has an important role in the news gathering process. The journalists stated that they use WhatsApp to get data like photos and videos from news sources.